1977
DOI: 10.3171/jns.1977.47.1.0019
|View full text |Cite
|
Sign up to set email alerts
|

A fast method of estimating the elastance of the intracranial system

Abstract: The authors describe a fast method for estimating the elastance of the intracranial system in man. The method consists in constructing the so-called amplitude-pressure (Amp-P) curve which describes the relationship between the amplitude of pulse-related oscillations in cerebrospinal fluid pressure and the basic level of intracranial pressure. The Amp-P curve consists of two straight lines, and the point of intersection of these lines is thought to indicate the intracranial pressure level at which there occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
2

Year Published

1983
1983
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 12 publications
6
51
0
2
Order By: Relevance
“…Our results are supported by findings in ten patients without intracranial pathology (Szewczykowski et al 1977), although no transitional phase was identified in that study. The Marmarou model is only valid for the upper, linear phase (Czosnyka et al 2004, Juniewicz et al 2005 and should according to the current study only be assumed for pressures above the transitional phase.…”
Section: Pulsatility Curve -Model Of the Relationship Between P And ∆Psupporting
confidence: 90%
“…Our results are supported by findings in ten patients without intracranial pathology (Szewczykowski et al 1977), although no transitional phase was identified in that study. The Marmarou model is only valid for the upper, linear phase (Czosnyka et al 2004, Juniewicz et al 2005 and should according to the current study only be assumed for pressures above the transitional phase.…”
Section: Pulsatility Curve -Model Of the Relationship Between P And ∆Psupporting
confidence: 90%
“…The whole-brain volume measurements were subsequently used to determine the variation of ICP. The established relationship between ICP and intracranial volume (Marmarou et al, 1975;Ryder et al, 1953;Sklar and Elashvili, 1977;Szewczykowski et al, 1977) is governed by the Monro-Kellie doctrine (Andrews and Citerio, 2004). In clinical practice, a measurement is made of the cerebrospinal fluid (CSF) expelled into a shunt or catheter, quantifying the pressure inside the skull and hence the change in brain volume.…”
Section: Magnetic Resonance Imaging: Brain Volumetrymentioning
confidence: 99%
“…A reduction in CSF significantly influences the elasticity of mechanical properties of the brain tissue (Kuroiwa et al, 2007). As the volume of the brain reaches the terminal disturbance level of ICP, the elasticity of the brain tissue tends to reduce as the brain swells and the CSF is driven from the system (Gefen et al, 2003;Muthupillai et al, 1995;Sklar and Elashvili, 1977;Szewczykowski et al, 1977). The reduction in CSF can also lead to hyponatremia.…”
Section: Fig 5 Depletion Of Cerebrospinal Fluid (Csf) Over the 5-h mentioning
confidence: 99%
“…Стабильность церебральной гемодинамики обусловлена функционированием сложной, многокомпонентной системы регуляции мозгового кровотока [12][13][14]. Помимо количе-ственной оценки каждого из внутричерепных объе-мов (мозговая ткань, кровь и ликвор), существенное значение имеет суммарная характеристика кранио-вертебральных объемных соотношений (КВОС), которая определяется как «теснота» (tightness) [15][16][17] всей цереброспинальной системы в целом. С этой целью изучается зависимость между дополни-тельным объемом, вводимым в ликворное про-странство, и возникающими при этом изменениями внутричерепного давления (ВЧД).…”
Section: методика собственных исследованийunclassified
“…С этой целью изучается зависимость между дополни-тельным объемом, вводимым в ликворное про-странство, и возникающими при этом изменениями внутричерепного давления (ВЧД). В качестве до-полнительного объема обычно используется сте-рильный физраствор, вводимый эндолюмбально, причем одновременно оцениваются изменения ВЧД (инфузионный тест) [15][16][17][18]. К сожалению, инвазивность этого метода значительно ограничи-вает возможности его клинического применения.…”
Section: методика собственных исследованийunclassified